Will the EU's Boat Float in Murky Post-Crisis Waters? An Assessment of EU's Economic and Financial Agenda - Adrian Daniel Stan; Brindusa Nicoleta Pincu (CES Working Papers, 2015)
The EU multilevel governance is a theoretical standpoint that allows us to measure the costs of nowadays European integration. This article addresses current issues of the EU institutional Agenda regarding the logic beyond the changing nature of the economic climate. Our contribution aims to analyze the impact of economic and financial reforms upon the institutional framework of the European Union. In this article we will explore how the post crisis economic agenda is being forged and which are the consequences of following different integration paths. It is also important to determine if a working scenario build around the Community method will address pressing issues in a successful manner or will the intergovernmental standpoint prevail? Is this crisis close to a positive response, is the EU economic governance an endangered construction, or can it be the rise of a great opportunity for the European integration process, a new boost each member state seeks and might nurture?
Keywords: E61; F15; F36; O23; P11; 330; governance; crisis; Community Method; Six Pack & Two Pack; fiscal reform